Strategi MSDM yang Efektif dalam Mendorong Pertumbuhan UMKM D'SRUPUT - Herliyani, Ramadhina; Annisa, Siti; Sandi, Santi Pertiwi Hari; Hidayaty, Dwi Epty (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This article discusses effective HRM strategies in driving the growth of UMKM D'SRUPUT. UMKM D'SRUPUT faces various challenges, including tight market competition, changing consumer trends, limited resources, and difficulty in building a strong brand. In facing these challenges, effective HR strategies are key to improving business performance and growth. In order to optimize HRM strategies, visits to industries/UMKM D'SRUPUT are important to learn successful practices in supporting UMKM growth. The method used for data collection in this article is structured interviews with D'SRUPUT entrepreneurs in Karawang Regency. The results of the industrial visits to UMKM D'SRUPUT describe D'SRUPUT that focuses on the food and beverage sector established in 2019. In starting the business, D'SRUPUT faced challenges competing with longer-established competitors. The conclusion of this article is that effective HR strategies are highly relevant in driving the growth of UMKM D'SRUPUT, and the advice given includes the application of these strategies, the use of appropriate technology, continuous evaluation and improvement, as well as visits to industries/UMKM D'SRUPUT to learn best practices in supporting UMKM growth.